PENGARUH PENERAPAN PENDEKATAN KONTESKTUAL TERHADAP KEMAMPUAN PEMECAHAN MASALAH DAN KEYAKINAN (BELIEF) MATEMATIKA SISWA KELAS IX SMP NEGERI 1 BAYANG - Dina Amsari (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2016)
This study was begun at finding description about the mathematics teacher did not make relationship between new information to real situation of students and the students ability in problem solving was still lower. This problem certainly impacts to mathematics belief of students. For making out this problem, a contextual approach in mathematics learning has been being applied. The goals of this research were to know students ability in problem solving between contextual and conventional approach and also mathematics belief of students after studied using contextual approach. The kind of this research was a quasi experiment. The population was the students of class IX Junior High School 1 Bayang. The researchs instruments are problem solving tests and questionnaire sheets. The result of this research showed the mean of final test in experiment class is higher than control class and also mathematics belief of student. Based on the result of the research could be conclude that students ability in problem solving and mathematics belief with using contextual approach better than conventional approach both high and low prior knowledges students. Kata kunci: pendekatan kontekstual, pemecahan masalah, keyakinan (belief) matematika